(untitled) (Alijtihed Journal on Legal and Economic Studies, 2023)
The General Agreement on Trade in Services, which came into force on 1 January 1995 with the creation of the World Trade Organization, applies to government measures affecting services provided on a commercial basis. The scope of the GATS is broader than the GATT applies to measures relating to goods. These rules, which are the subject of this section apply to services and service providers, are prescribed in the articles that constitute the legal text of the Agreement.